ARTIKEL REVIEW : BAKTERI NITRITASI DAN PERANANNYA DALAM KEBERADAAN NITRIT PADA SARANG BURUNG WALET - Widiyani, Platika; Latif, Hadri; Lukman, Denny W.; Sudarwanto, Mirnawati B. (JURNAL KAJIAN VETERINER, 2021)
Edible bird nest is a high-value export commodity. The industry of edible bird nests encounters various challenges regarding food safety demands for consumers, especially related to the quality of edible bird nests and compliance of nitrite below 30 ppm for the export commodity to China. The purpose of this paper is to obtain information on nitrate content in edible bird nests, the impact of nitrite on consumers and mechanism of nitrite, nitrification processes and mechanisms of nitrification in nature, types of nitrifying bacteria, the nitrification process, and the role of nitrifying bacteria in the edible bird nests, and also nitrite testing methods. This paper shows the nitrite content in edible bird nests at various levels. Nitrite is toxic and dangerous. Nitrite can cause methemoglobinemia, impaired oxygen flow, and difficulty breathing. Hygiene conditions and the environment of the swallow’s house can affect the amount of nitrite in the edible bird nest. Alteration in nitrite can occur through changes in nitrogen in the air to nitrite. Nitrite forming in edible bird nests is a natural process of shift nitrogen in the swallow's house environment and influenced by nitrite-producing bacteria were found in swallow's houses and converting nitrate to nitrite. Nitrification bacteria are bacteria that important role in increasing organic content and the availability of nutrients in the soil by providing nitrate. There are a few bacteria nitrification find in nature and edible bird nests such as Nitrosomonas Sp, Nitrobacter Sp, Nitrospina Sp, Nitrosococcus Sp, Nitrocystis Sp, and Bradyrhizobium japonicum.